2019
DOI: 10.3892/ol.2019.11193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hub genes on the clinicopathological and prognostic features of lung adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) is a common malignancy; however, the majority of its underlying molecular mechanisms remain unknown. In the present study, weighted gene co-expression network analysis was applied to construct gene co-expression networks for the GSE19804 dataset, in order to screen hub genes associated with the pathogenesis of LUAD. In addition, with the aid of the Database for Annotation, Visualization and Integrated Discovery, Gene Ontology, and Kyoto Encyclopedia of Genes and Genomes, pathway enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…It participates in a variety of biological processes, including respiration, calcification, acid-base balance, bone resorption, and formation of aqueous humor, cerebrospinal fluid, saliva, and gastric acid. It is down-expressed in human LUAD tissues (Yu et al, 2020) and promotes the proliferation of cancer cells (Chen et al, 2017). The prognosis of LUAD, KIRC and LGG patients with low expression of CA4 is poor, which is consistent with the findings in colorectal cancer and renal cell carcinoma (Takenawa et al, 1998;Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 81%
“…It participates in a variety of biological processes, including respiration, calcification, acid-base balance, bone resorption, and formation of aqueous humor, cerebrospinal fluid, saliva, and gastric acid. It is down-expressed in human LUAD tissues (Yu et al, 2020) and promotes the proliferation of cancer cells (Chen et al, 2017). The prognosis of LUAD, KIRC and LGG patients with low expression of CA4 is poor, which is consistent with the findings in colorectal cancer and renal cell carcinoma (Takenawa et al, 1998;Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 81%
“…The 3’-UTR of GIMAP6 contained hypothetical binding sites for miR-24-3p ( Figure 5A ). GIMAP6 was reported to be associated with LUAD ( 24 , 25 ) and was therefore chosen for subsequent experiments. The expression levels of GIMAP6 in LUAD and its association with survival were determined using the GEPIA database.…”
Section: Resultsmentioning
confidence: 99%
“…PECAM1 can code for CD31, belonging to the immunoglobulin superfamily of adhesion molecule, which can maintain and restore vascular integrity by the wingless-related integration site signaling pathway [ 28 ]. Yu et al analyzed the related microarray datasets (GSE9804) and identified that PECAM1 played a crucial role in the tumorigenesis of LUAD via regulation of vascular endothelial growth factor (VEGF) expression [ 29 ]. The mRNA transcription and the protein expression levels, we found that PECAM1 expression was significant down-regulated in LUAD tumor tissues.…”
Section: Discussionmentioning
confidence: 99%